3D joint inversion of airborne ZTEM and ground MT data using the finite element method with unstructured tetrahedral grids - Cao, Xiaoyue; Huang, Xin; Yan, Liangjun; Ben, Fang; Li, Jianhua (Frontiers in Earth Science, 2023)
As an airborne EM method induced by natural sources, the Z-Axis tipper electromagnetic (ZTEM) can mainly recover the near-surface shallow structures, due toand high sample rate acquisition along the terrain. traditional ground magnetotelluric (MT) allows better recovery of deep structures as the data acquired are typical of large site intervals (usually higher than 1 km) and lower frequencies (usually lower than 400 Hz). As the 1D structures produce zero vertical magnetic fields, ZTEM is not sensitive to the background resistivity. Thus, in general, ZTEM can only reveal relative resistivities but not real resistivities. A combination of the ZTEM and MT data can be an effective technique, alleviating the shortcomings of the individual methods. Nowadays, the complex underground structures and topography introduce difficulties for data inversion and interpretation, as the conventional ZTEM and MT forward modeling is generally used on structured grids with limited accuracy. To effectively recover the complex underground structures with topography, the finite element method is used for the forward problem because of its flexibility with unstructured tetrahedral meshes. And the limited-memory quasi-Newton algorithm (L-BFGS) for optimization is used to solve the joint inverse problem, which saves memory and computational time by avoiding the explicit calculation of the Hessian matrix. To validate our joint inversion algorithm, we run numerical experiments on two synthetic models. Both single domain and joint inversions of the ZTEM and MT data are carried out for the two synthetic models to demonstrate the complementary advantages of the joint inversion, while the second model is also used to test the adaptability of the joint inversion to the topography. The results have demonstrated the effectiveness of the finite element method with unstructured tetrahedral grids and the L-BFGS method for joint MT and ZTEM inversion. In addition, the inversion results have proved that joint tradictional MT and ZTEM inversion can recover deep structures from the MT data and delicate near-surface structures from the ZTEM data by alleviating the weaknesses of the individual methods.